Avaliação de clones de seringueira quanto à resistência ao oídio - Tumura, Karina Goulart [UNESP] (2013)
Five commercial rubber tree clones in a clonal nursery were assessed for resistance to powdery mildew, as well as for the disease fluctuation and its correlation with the climate conditions in the study period. For this assessment, a diagrammatic scale was developed from 150 central leaflets randomly collected at different ages and attack levels. Validation of scale was done by five assessors. Results indicated that all clones showed susceptibility to the pathogen, and the attack was higher for younger leaflets. According to the climate data, mild temperatures and relative humidity below 60% favored the epidemic.